2018
DOI: 10.21608/ejabf.2018.16562
|View full text |Cite
|
Sign up to set email alerts
|

Growth response, nutrient utilization, biochemical and hematological parameters of Juvenile African catfish (clarias gariepinus) fed diet supplemented with gongronema latifolia (benth) extract.

Abstract: This study investigated the effect of varying levels of Gongronema latifolia on growth, nutrient utilization, biochemical and hematological parameters of Clarias gariepinus juveniles. One hundred and five (105) juveniles were equally distributed in fifteen plastics tanks and each triplicated. Three inclusion levels of the plant extract (150mg/kg, 300mg/kg and 500mg/kg) were prepared, while the antibiotics served as negative control and the diet without any inclusion served as the positive control. The fish mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…In this study, the content of LZM in fish increased under cooling stress, but the content of LZM in E3 treatment group was significantly lower than that in E1 and E2 treatment groups, indicating that vitamin E treatment could alleviate stress and reduce immune response. The ALP is produced by intrahepatic bile duct cells and is an important marker of liver dysfunction [28][29][30]. In the study of rohu (Labeo rohita), it was found that the ALP activity of rohu was significantly increased under DEP toxicity stress [31].…”
Section: Effects Of Vitamin E On Blood Physiological and Biochemical ...mentioning
confidence: 99%
“…In this study, the content of LZM in fish increased under cooling stress, but the content of LZM in E3 treatment group was significantly lower than that in E1 and E2 treatment groups, indicating that vitamin E treatment could alleviate stress and reduce immune response. The ALP is produced by intrahepatic bile duct cells and is an important marker of liver dysfunction [28][29][30]. In the study of rohu (Labeo rohita), it was found that the ALP activity of rohu was significantly increased under DEP toxicity stress [31].…”
Section: Effects Of Vitamin E On Blood Physiological and Biochemical ...mentioning
confidence: 99%